2008
DOI: 10.1007/s11695-008-9548-1
|View full text |Cite
|
Sign up to set email alerts
|

The Bone-Adipose Axis in Obesity and Weight Loss

Abstract: Body fat and lean mass are correlated with bone mineral density, with obesity apparently exerting protection against osteoporosis. The pathophysiological relevance of adipose tissue in bone integrity resides in the participation of adipokines in bone remodeling through effects on deposition and resorption. On the other hand, the skeleton has recently emerged as an endocrine organ with effects on body weight control and glucose homeostasis through the actions of bone-derived factors such as osteocalcin and oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
86
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(93 citation statements)
references
References 120 publications
(192 reference statements)
4
86
0
3
Order By: Relevance
“…White adipose tissue (WAT) is the most abundant form, found in both subcutaneous and intraabdominal regions. WAT was first regarded only as an energy reservoir, however it is now well recognized as an endocrine organ due to its secretion of circulating adipokines and pro-inflammatory factors [14][15][16][17][18][19][20] . Obesity, defined as an abundance of WAT, has always been depicted as a protective factor against the development of bone loss and osteoporosis [5,6] , nevertheless several groups, including ours [11][12][13] , have recently demonstrated that high amounts of adipose tissue accumulation might not be considered a protective factor against the development of osteoporosis and fracture risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…White adipose tissue (WAT) is the most abundant form, found in both subcutaneous and intraabdominal regions. WAT was first regarded only as an energy reservoir, however it is now well recognized as an endocrine organ due to its secretion of circulating adipokines and pro-inflammatory factors [14][15][16][17][18][19][20] . Obesity, defined as an abundance of WAT, has always been depicted as a protective factor against the development of bone loss and osteoporosis [5,6] , nevertheless several groups, including ours [11][12][13] , have recently demonstrated that high amounts of adipose tissue accumulation might not be considered a protective factor against the development of osteoporosis and fracture risk.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, adipose tissue not only stores excess triacylglycerols, but functions as an endocrine organ by releasing several adipokines, which appear to modulate glucose and lipid metabolism, inflammation, appetite and insulin resistance [14][15][16] . Additionally, the physiological relevance of adipose tissue for skeletal health likely resides in the role that some of these adipokines, such as interleukin (IL)-6 and tumor necrosis factor-α (TNF-α), might play by interfering with bone cells homeostasis [17][18][19][20] . Moreover, bone has started to be considered an endocrine organ itself affecting both body weight control and glucose homeostasis through the action of bone-derived factors such as osteocalcin and osteopontin [21,22] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to adipose tissue, bone tissue has also emerged as endocrine organ that produces several osteokines with potential effects on energy homeostasis (6). Specifically, osteocalcin that has been traditionally considered a biological marker of bone formation has effects on body mass, energy expenditure (EE), and glucose homeostasis (6,8). It has been found that osteocalcin is not affected by menstrual cycle phase similar to adiponectin in female rowers (20).…”
Section: Introductionmentioning
confidence: 99%
“…The putative mechanism relevance of adipose tissue for skeletal integrity probably resides in the role of several adipokines in bone remodeling through effect on both formation and resorption. Recently, bone has been considered an endocrine organ affecting body weight control and glucose homoeostasis through the actions of bone-derived factors such as osteocalcin and osteopontin [21][22][23][24] .…”
Section: Discussionmentioning
confidence: 99%